Collembola Poduromorpha from Guelma Province (Northeastern Algeria), with description of a new Superodontella species (Collembola: Odontellidae) - Arbea, Javier I.; Brahim-Bounab, Hayette; Kroua, Salah Hamra (Zootaxa, 2013)
Ten Poduromorpha species have been found in the Taya Region, three of which are new for Algeria: Hypogastrura vernalis (Carl, 1901), Xenylla brevisimilis mediterranea Gama, 1964 and Superodontella tayaensis sp. nov. The new species is morphologically closest to S. subalpina Arbea, 1990, with three subequal dental chaetae. They differ in the number of tibiotarsal chaetae and the sensilar chaetotaxy of Ant IV.